The TAIGA experiment: from cosmic ray to gamma-ray astronomy in the Tunka valley. Issue 5 (May 2016) - Budnev, N; Astapov, I; Bezyazeekov, P; Bogdanov, A; Boreyko, V; Büker, M; Brückner, M; Chiavassa, A; Chvalaev, O; Gress, O; Gress, T; Grishin, O; et al.
Abstract: The physical motivations and advantages of the new gamma-observatory TAIGA (Tunka Advanced Instrument for cosmic ray physics and Gamma Astronomy) is presented. The TAIGA array is a complex, hybrid detector for ground-based gamma-ray astronomy for energies from a few TeV to several PeV as well as for cosmic ray studies from 100 TeV to several EeV. The TAIGA will include the wide angle Cherenkov array TAIGA-HiSCORE with ~5 km 2 area, a net of 16 I ACT telescopes (with FOV of about 10x10 degree), muon detectors with a total area of up to 2000-3000 m 2 and the radio array Tunka-Rex.